Assessing effective pasture root depth for irrigation scheduling by water balance and soil moisture monitoring. (25th March 2022) - KC, Birendra; Schultz, Bart; Mohssen, Magdy; Chau, Henry Wai; Pandey, Vishnu Prasad; Prasad, Krishna; Anthony, Patricia
Abstract: The 'effective' root depth of perennial ryegrass used for irrigation scheduling has substantial implications when estimating irrigation requirements. This study included field measurements of 20 percolation lysimeters with diameters and heights of 500 and 900 mm, respectively, installed on the Lincoln University Dairy Farm, Christchurch, New Zealand, to estimate actual evapotranspiration (ETa ) based on water balance analysis for three soil depths: 500, 600 and 700 mm. Reference evapotranspiration (ETr ) was estimated based on the CropWat 8 model. Perennial ryegrass height ( h cm) was measured for each lysimeter. Among the three soil depths, 500 mm produced the highest regression coefficient for the crop coefficient ( K c = ETa /ETr ) and h relationship. The results indicate the need to consider a 500 mm root depth to estimate irrigation requirements on this farm to achieve optimal water productivity. A noticeable fluctuation in daily soil water content for the top 500 mm soil profile, measured in time domain reflectometry probes and with an Aquaflex soil moisture sensor, also reinforces the earlier statement. Résumé: La profondeur 'efficace' des racines de ray‐grass vivace utilisée pour la planification de l'irrigation a des conséquences importantes sur l'estimation des besoins en irrigation. Cette étude comprenait des mesures sur le terrain de 20 lysimètres à percolation avec des diamètres et des hauteurs de 500 et 900 mm, respectivement, installés sur la ferme laitière de l'Université Lincoln, Christchurch, Nouvelle‐Zélande, pour estimer l'évapotranspiration réelle (ETa) basée sur l'analyse du bilan hydrique de trois profondeurs de sol: 500, 600 et 700 mm. L'évapotranspiration de référence (ETr) a été estimée sur la base du modèle CropWat 8. La hauteur de ray‐grass vivace (h cm) a été mesurée pour chaque lysimètre. Parmi les trois profondeurs de sol, 500 mm ont produit le coefficient de régression le plus élevé pour le coefficient de culture (Kc = ETa/ETr) et la relation h. Les résultats indiquent la nécessité de tenir en compte une profondeur d'enracinement de 500 mm pour estimer les besoins en irrigation de cette ferme afin d'atteindre une productivité optimale de l'eau. Une fluctuation visible de la teneur en eau quotidienne du sol pour le profil supérieur de 500 mm, mesurée dans les sondes de réflectométrie dans le domaine temporel et avec un capteur d'humidité du sol Aquaflex, renforce également l'exposition précédente.